An Evaluation of English Podcast Come and Speak Hour Program - Lia Sulistiawati; Muchlas Suseno (LETS: Journal of Linguistics and English Teaching Studies, 2022)
Podcasts are one of the most popular technological tools for language acquisition. Podcasts, which are digital recordings, can be used to help students learn English, especially in the areas of listening and speaking. Because of that the language team of Nurul Fikri Boarding School, Serang-Banten created the podcast CASH (Come and Speak Hour) program to improve students listening and speaking skills. This study reviews the impact of using podcasts in supporting language learning. As a tool, podcasts have the power to enhance students learn English. The method used is survey and observation through podcast rubric by digital blooms’ taxonomy framework. 40 students of SMAI NFBS are chosen as the participants. From the survey, it is found that podcast is interesting and beneficial for the student in improving English skills & the characteristics of 4Cs. However, only a few students that are 15% said that they want to involve in that program, and based on observation some improvements are likely needed to make the quality of the podcast better so that the involvement and engagement of students increase. Thus, eventually, it will give more benefits to them